WORKSHOP DAN PENDAMPINGAN PUBLIKASI KARYA TULIS ILMIAH BAGI GURU SDN 5 PARIJATAH KULON - Qori'ah, Maria; Andriyanto, Dicky; Viana, Ria Octa (Yayasan Sagita Akademia Maju, 2024)
This service is carried out as an effort to increase teacher competence in the context of developing the quality of education which is realized in the form of scientific papers. Writing scientific papers is a mandatory requirement for improving the teaching profession. The phenomenon that exists is that teachers tend to have difficulty in preparing it because they have little insight into the publication of scientific papers. Therefore, it is necessary to hold outreach activities and assist in the preparation and publication of scientific papers. The aim of this service is so that teachers have the insight and skills to write scientific papers according to the rules of good and correct writing so that they are published in reputable journals. This service method uses service learning where teachers are involved in activities to improve writing skills. The activity material is in the form of the importance of publications and the basis for preparing scientific papers. As a result of this service, teachers understand and publish scientific papers in their respective field.